2022
DOI: 10.1186/s40168-022-01327-7
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the antibiotic resistome of preterm infants reveals new benefits of probiotic supplementation

Abstract: Background Probiotic use in preterm infants can mitigate the impact of antibiotic exposure and reduce rates of certain illnesses; however, the benefit on the gut resistome, the collection of antibiotic resistance genes, requires further investigation. We hypothesized that probiotic supplementation of early preterm infants (born < 32-week gestation) while in hospital reduces the prevalence of antibiotic resistance genes associated with pathogenic bacteria in the gut. We used a targeted captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…The analysis must consider if the probiotic is being developed for broad distribution to generally healthy consumers (foods or supplements, for which a reasonable certainty of no harm is the general standard) or restricted distribution for patient populations (drugs). Since probiotics have the potential to exacerbate 54 or mitigate 55 the reservoir of AR genes harbored in humans, a case-by-case approach to safety is likely needed. Previous authors have suggested systematic approaches to considering this issue.…”
Section: Acute Risksmentioning
confidence: 99%
“…The analysis must consider if the probiotic is being developed for broad distribution to generally healthy consumers (foods or supplements, for which a reasonable certainty of no harm is the general standard) or restricted distribution for patient populations (drugs). Since probiotics have the potential to exacerbate 54 or mitigate 55 the reservoir of AR genes harbored in humans, a case-by-case approach to safety is likely needed. Previous authors have suggested systematic approaches to considering this issue.…”
Section: Acute Risksmentioning
confidence: 99%
“… Azithromycin, erythromycin 25 Macrolides Respiratory, intestine, gynecological, urogenital and skin infections, chlamydia infections and syphilis. Ciprofloxacin, norfloxacin 26 , 27 Quinolones Serious gram-negative bacterial infections. Clindamycin 28 , 29 Lincomycin Respiratory, skin, blood, female reproductive organ, and internal organ infections.…”
Section: Antibiotics In Mother-infant Dyadsmentioning
confidence: 99%
“…In premature babies, probiotic supplementation may increase protection against harmful bacteria and reduce the negative impact of antibiotics on the microbiome and resistome of the gut 26 . A different study demonstrated that administering probiotics to preterm infants during hospitalization after birth decreased the gut microbiome’s resistance gene diversity and prevented its persistence 27 .…”
Section: How Can We Reduce Antibiotic Resistance In Mother-infant Dyads?mentioning
confidence: 99%
“…Analysis of Target Capture Sequencing Data. Sequenced reads were analyzed as described by Guitor et al 19 with a few modi cations. Paired sequencing reads were trimmed using skewer (version 0.2.2) 20 and deduplicated using dedupe.sh from BBMap (version 38.57) 21 .…”
Section: Drug Administrationmentioning
confidence: 99%